Study of changes in mechanical properties of 3D elements of printed products under the influence of ultraviolet radiation - Kyrychok, T.; Klymenko, T.; Volodko, M. (ТОВ «Видавництво Ліра-К», 2025)
An overview of the main digital technologies (AR, VR, AI, and digital printing methods) used in the design, development, and manufacturing of packaging products throughout their life cycle is provided.
Keywords: digital printing; digital technologies